2009
DOI: 10.1016/j.ceb.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells, microenvironment mechanics, and growth factor activation

Abstract: Physicochemical features of a cell's microenvironment can exert important effects on cell behavior and include the effects of matrix elasticity on cell differentiation processes, but molecular mechanisms are largely mysterious. Here we highlight recent reports of a mechanical dependence to growth factor activation, with a particular focus on release of TGFβ (Transforming Growth Factor β) from its large latent complex via forced unfolding. We discuss these processes and pathways in the contexts of matrix adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…The impact of forces and mechanical environment on the structure and function of cells and tissues has been increasingly documented in many recent studies and summarized in recent reviews (Mammoto and Ingber, 2010;Tenney and Discher, 2009;Vogel and Sheetz, 2009). Many of these research efforts have been directed at demonstrating that physical features such as stiffness are direct stimuli for specific cellular responses, rather than attributable to biochemical differences in the substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of forces and mechanical environment on the structure and function of cells and tissues has been increasingly documented in many recent studies and summarized in recent reviews (Mammoto and Ingber, 2010;Tenney and Discher, 2009;Vogel and Sheetz, 2009). Many of these research efforts have been directed at demonstrating that physical features such as stiffness are direct stimuli for specific cellular responses, rather than attributable to biochemical differences in the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In this Commentary, we discuss the differences between physical and chemical stimuli that can influence cell and tissue function, and consider the fundamental mechanisms that might enable cells to measure the stiffness of the extracellular matrix and of neighboring cells. Candidate proteins and signals that are involved in sensing or responding to forces and might also be relevant to stiffness sensing have been well discussed in other recent reviews (Koivusalo et al, 2009;Kumar and Weaver, 2009;Mammoto and Ingber, 2010;Tenney and Discher, 2009;Vogel and Sheetz, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Especially during development, epithelial cells grow, divide and move, leading to a dynamic reorganisation of the entire tissue. This process is regulated by a complex set of chemical and mechanical signalling pathways [1][2][3][4] that control cell shapes and cell-cell contacts. How the regulation of cell-cell interactions is transmitted to the tissue-level organisation is still a topic of active research.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a biomimetic microenvironment that can guide cell differentiation is a very powerful tool in regenerative medicine. 25 In this study, we built an artificial niche for vascular tissue formation from BMNCs by combining the soft elastomeric PGS and platelets and plasma. We found that diluted plateletpoor plasma and platelets could be coated onto the porous structure of the PGS scaffolds.…”
Section: Discussionmentioning
confidence: 99%